Analysis of elastic arches three-hinged, two-hinged, and hingeless of steel, masonry, and reinforced concrete - Balet, Joseph W. (Archibald Constable, 1908)
Presenting a new system for the application of the elastic theory to the analysis of the stresses in arches, the author shows that streses are obtained with absolute certainty.